214k views
1 vote
I need answer as quick

I need answer as quick-example-1

2 Answers

0 votes

Answer:

C

Explanation:

Given

(x + 7)(x + 1)(x + 4) ← expand the second/ third factors using FOIL

= (x + 7)(x² + 5x + 4)

= x(x² + 5x + 4) + 7(x² + 5x + 4) ← distribute both parenthesis

= x³ + 5x² + 4x + 7x² + 35x + 28 ← collect like terms

= x³ + 12x² + 39x + 28 → C

User Roly
by
5.1k points
6 votes

Answer:

C

Explanation:

(x+7)(x+1)(x+4)=

x^3+12x^2+39x+28 or C

User Linus Borg
by
4.9k points